Development of Eco-Friendly and Child Oriented Concepts in the Interior Design of Jakarta’s Child-Friendly Public Spaces - Shirly Angela; Lu’lu’ Purwaningrum (TAMA: Journal of Visual Arts, 2025)
As a downtown area with high population density, the Jakarta City Government is committed to creating an interior Child Friendly Integrated Public Space (RPTRA) with the concept of a safe and supportive environment for children in urban areas. With an increasing population, Jakarta needs more RPTRAs for effective educational facilities for children's growth and development. The Interior Design of RPTRA in Jakarta was created to respond to parents' concerns about the lack of adequate educational facilities. The Eco Friendly concept is applied to create an interior environment that supports children's well-being by integrating natural elements and eco-friendly materials. The research method involves a literature study to understand the concept of Eco Friendly and children's interior design needs, as well as site analysis and case studies of RPTRAs in Jakarta. The result is an RPTRA interior design that prioritizes building according to green building standards, utilizing used materials that are still suitable for interior elements, and child-friendly sensory stimulation, with a focus on natural elements such as plants visually, and the use of natural lighting. The design also considers the flexibility of the space to support children's various educational, rehabilitative, and recreational activities. It is hoped that the implementation of this design will create an engaging learning experience and increase children's awareness of the importance of education.